Biofabrication and Characterization of Zinc Oxide Nanoparticles Using Staphylococcus aureus - Najeeb, Venus D.; Ali, Fattma A.; Swilaiman, Sameira S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
Due to their large surface area and catalytic properties, zinc oxide nanoparticles (ZnO-NPs) are highly effective in biological applications. In this study, ZnO-NPs were biofabricated using the American Type Culture Collection Staphylococcus aureus (ATCC 25923) and characterized by double-beam ultraviolet-visible spectroscopy, with a characteristic absorption peak at 351 nm, verifying the synthesis of ZnO-NPs. Proteins and carboxyl and hydroxyl groups that function as reducing and stabilizing agents were found on the surface of biosynthesized ZnO-NPs, as revealed by Fourier transform infrared analysis. The hexagonal structure was validated by X-ray diffraction analysis. Spherical shape confirmed by Field Emission Scanning Electron Microscopy, and the main elements detected by energy-dispersive spectroscopy were Zinc 79.91% and oxygen 18.33%. Transmission electron microscopy investigation revealed that the ZnO-NPs produced were predominantly quasi-spherical to irregular shape, with diameters in the nanoscale range (approximately 40–60 nm). The results indicated that the diameter of inhibitory zones against methicillin resistant S. aureus (MRSA) using varying concentrations of 50, 25, 12.5, 6.25, and 3.125 μg/mL of ZnO-NPs in an agar well diffusion test ranged from 7 to 24 mm, and the cytotoxicity of ZnO-NPs was assessed by MTT assay. Human embryonic kidney 293 cells were used. Our research demonstrates that biofabricated ZnO-NPs using standard S. aureus exhibit successful characterization and strong anti-MRSA activity, which may represent a promising path for the development of innovative antimicrobial agents, particularly for treating MRSA as multidrug-resistant isolates.